A Prototype towards a Physical and Logical Architecture: Varela House - Olóriz Sanjuán, Clara (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
Alejandro de la Sota’s approach towards prefabrication re-defines architecture as a material practice. More in particular, his ways of ‘projecting’ with the Horpresa system in the Varela House respond to the challenge of designing a repeatable test-bed or ´microscopic preparation for great experiences’ to address his contemporary conditions in housing demands. This essay introduces Sota’s critical approach towards prefabrication from his notions of physical and logical architecture. These concepts will be developed through his application of the Horpresa panels: How they influenced his way of thinking, projecting, designing with the system from the prototype (Varela House) to the large scale (Orense and Bahia Bella complex) by means of spatial patterns and combinatorial assemblages. This reflection will address the relationship between the Horpresa system and Sota’s projects, between means and ends, between technology or the new materials and architectural production.
Keywords: Prefabrication; Horpresa; System; Prototype; Grid; Assembly